Clinical practice guidelines for the care of girls and women with Turner syndrome - Gravholt, Claus H; Andersen, Niels H; Christin-Maitre, Sophie; Davis, Shanlee M; Duijnhouwer, Anthonie; Gawlik, Aneta; Maciel-Guerra, Andrea T; Gutmark-Little, Iris; Fleischer, Kathrin; Hong, David; Klein, Karen O; Prakash, Siddharth K; et al. (European journal of endocrinology, 2024)
Turner syndrome (TS) affects 50 per 100 000 females. TS affects multiple organs through all stages of life, necessitating multidisciplinary care. This guideline extends previous ones and includes important new advances, within diagnostics and genetics, estrogen treatment, fertility, co-morbidities, and neurocognition and neuropsychology. Exploratory meetings were held in 2021 in Europe and United States culminating with a consensus meeting in Aarhus, Denmark in June 2023. Prior to this, eight groups addressed important areas in TS care: (1) diagnosis and genetics, (2) growth, (3) puberty and estrogen treatment, (4) cardiovascular health, (5) transition, (6) fertility assessment, monitoring, and counselling, (7) health surveillance for comorbidities throughout the lifespan, and (8) neurocognition and its implications for mental health and well-being. Each group produced proposals for the present guidelines, which were meticulously discussed by the entire group. Four pertinent questions were submitted for formal GRADE (Grading of Recommendations, Assessment, Development and Evaluation) evaluation with systematic review of the literature. The guidelines project was initiated by the European Society for Endocrinology and the Pediatric Endocrine Society, in collaboration with members from the European Society for Pediatric Endocrinology, the European Society of Human Reproduction and Embryology, the European Reference Network on Rare Endocrine Conditions, the Society for Endocrinology, and the European Society of Cardiology, Japanese Society for Pediatric Endocrinology, Australia and New Zealand Society for Pediatric Endocrinology and Diabetes, Latin American Society for Pediatric Endocrinology, Arab Society for Pediatric Endocrinology and Diabetes, and the Asia Pacific Pediatric Endocrine Society. Advocacy groups appointed representatives for pre-meeting discussions and the consensus meeting.